Scientific and Pedagogical Heritage of Professor V.L. Wagin at the Kazan University - R.M. Sabirov; A.I. Golubev; L.V. Malutina; A.V. Bespyatikh (Учёные записки Казанского университета: Серия Естественные науки)
The scientific and educational materials of Professor V.L. Wagin related to the Kazan period of his life and stored in the archive of the Department of Zoology and General Biology, Kazan Federal University have been described. His research work in Kazan followed three main directions: 1) systematics and development of Ascothoracida crustaceans, parasites of echinoderms and coral polyps; 2) phylogeny of Myzostomida worms, ecto- and endoparasites of echinoderms; 3) parasitology of fish inhabiting water bodies of the Middle Volga Region, in particular the Kuybyshev Reservoir. The first and second directions are associated with the development of V.L. Wagin's research during the pre-Kazan period of his life, in the Arctic expeditions and Leningrad. When V.L. Wagin worked in Kazan, he added to the already available data on myzostomid worms and ascothoracid crustaceans by participating in the intercollegiate expeditions on the “Bataysk” research vessel (1960-1963) to the Barents Sea, Norwegian Sea, and North Atlantic. The third direction of research was developed by V.L. Wagin at the Kazan University. He published a total of 37 scientific articles in Kazan out of the 60 articles comprising the entire list of his publications. There are original sketches of Ascothoracida and Myzostomida, worksheets, more than 50 educational tables, unique collection of museum preparations in the archives of the Department of Zoology and General Biology, Kazan Federal University. The lectures delivered by V.L. Wagin on invertebrate zoology, parasitology, zoogeography, comparative embryology turned out to be a good example of professional lecturing skills and teaching excellence.